Designing authoritarian deliberation: how social media platforms influence political talk in China. Issue 2 (17th February 2020) - Stockmann, Daniela; Luo, Ting; Shen, Mingming
ABSTRACT: Discussion is often celebrated as a critical element of public opinion and political participation. Recently, scholars have suggested that the design and features of specific online platforms shape what is politically expressed online and how. Building on these findings and drawing on 112 semi-structured qualitative interviews with information technology experts and internet users, we explain how major Chinese social media platforms differ in structure and motivation. Drawing upon a nationwide representative survey and an online experiment, we find that platforms aiming to make users a source of information through public, information-centred communication, such as the Twitter-like Weibo, are more conducive to political expression; while platforms built to optimize building social connections through private, user-centred communication, such as WhatsApp and Facebook-like WeChat, tend to inhibit political expression. These technological design effects are stronger when users believe the authoritarian state tolerates discussion, but less important when political talk is sensitive. The findings contribute to the debate on the political consequences of the internet by specifying technological and political conditions.